Does the Permanent Establishment article give Namibia adequate taxing rights?An analysis of tax convention models in the mining and fishing industries - Swartz, Rikotoka Punaje (Department of Finance and Tax, 2019)
Namibia is a country rich in natural resources and heavily dependent on foreign investment to effectively make use of those resources. It has a national policy of encouraging investment from other countries and has set up incentives for that purpose. When there is a great deal of involvement of foreign companies in a country, international tax issues of judicial double taxation are discouraging to foreign investors. In an effort to address this risk, Namibia has entered into various double tax agreements with countries to ensure equitable taxing rights and encourage foreign direct investment. Double tax agreements are usually based on model tax agreements published by large international organisations, the most popular being the Organisation for Economic Cooperation and Development (“OECD”) and United Nations (“UN”). The African Tax Administration Forum (“ATAF”) has also recently formulated such a model for African countries. As Namibia has a source based taxation system, giving up any taxing rights are of great concern and it must consider if these double tax agreements is in its best interest. Subsequently, Namibia has begun the process of renegotiating its tax treaties with other countries in hope of sacrificing fewer source taxing rights. This dissertation analyses Namibia’s current double tax agreements to determine whether the permanent establishment article offers sufficient protection for Namibia’s source taxing rights with reference to Namibia’s largest and most important industries of fishing and mining. The permanent establishment article is of particular importance as it usually provides an unrestricted taxing right to the income in the source country in which the permanent establishment is based. This study considers the permanent establishment article as it applies to the fishing and mining industries in Namibia. This includes a discussion of the mining and fishing industries in Namibia and a brief look at the applicable taxation regime. It also compares the permanent establishment article found in the OECD, UN and ATAF models to discuss which represents the most appropriate for Namibia to use as the basis for its renegotiations. The agreements analysed do show some areas for concern to Namibia namely: • The treaty with the United Kingdom is very out dated and may not give Namibia full territorial rights. • Many of the treaties with developed countries have permanent establishment article that are based more on the OECD model than the UN model which is specifically designed to give developing countries more taxing rights. • The permanent establishment article in the ATAF model gives the most taxing rights to the host/source country and has specific provisions negating the risk of abuse by foreign companies. However, there is a concern that such provisions may have too wide a scope and discourage foreign investment. • Most of the provisions of potential benefit to Namibia have been inserted in Article 5(2) and are arguably ineffective or less effective protections. • Namibia’s current DTAs contain no provisions directly related to fishing vessels which is of concern as fishing vessels are at risk of not being classified as permanent establishments. There are, however, arguments to be made for a fishing vessel as a mobile place of business forming a permanent establishment without such special provision. • A specific deeming provision regarding the permanent establishment in the exploration phase of the mining process would be advisable if Namibia wished to create one in the mining industry as soon as possible.